Impact of an extramural program in training dental students (Revista da Faculdade de Odontologia - UPF, 2012)
Introduction: Extramural programs allow dental students to be trained facing the reality of people’s lives and their health needs. This study describes the experiences of an extramural program developed at the Federal University of Santa Maria, RS, Brazil. Methods: Professors and dentists participated in activities directed to a group of recyclable material collectors and their families, who are part of a singing group. The aim of the activities is to provide dental care, health promotion, health education and disease prevention. Results: Up until now, 80 people have been involved in the program. It was possible to observe that the collectors have gained confidence and self-esteem and positive changes in their behavior regarding health. The academic training was enriched by the educational, clinical and humanistic experience by interacting with the social context of the collectors. Conclusion: An endeavor to improve the health of these people has guaranteed an opportunity to train the health professional in a qualified teaching and learning environment in front of social reality.